Inflammatory heart diseases in children - Tatjana Gavrilović-Elez; Vladimir Čančar; Nada Avram; Biljana Milinković; Dejan Bokonjić (Биомедицинска истраживања, 2019)
Myocarditis is a limited or diffuse inflammation of the heart muscle, the cause of which might be infectious (viruses, bacteria, fungi, rickettsiae, parasites, protozoas) or non-infectious (systemic diseases, metabolic diseases, toxins). There are types of myocarditis the etiological factor of which cannot be determined and therefore are classified into the group of idiopathic myocarditis. The clinical picture depends on the intensity of the inflammatory process and the lesion topography, varying from a mild form of the disease to severe malignant myocarditis followed by the development of cardiac insufficiency as well as by fatal outcome within a few days. Resting is recommended as the basic method of therapy in all of the patients with suspected myocarditis. If there are signs and symptoms of cardiac insufficiency, an anticongestive therapy must be introduced (diuretics, vasodilators, digitalis). If the conventional therapy does not produce the desired results, it is necessary to introduce continuous intravenous inotropes (dobutamine or phosphodiesterase inhibitors). Rhythm disorders in patients with myocarditis require an appropriate antiarrhythmic drug therapy that should be given as soon as possible. Acute pericarditis is an inflammation of the pericardium characterized by chest pain, pericardial friction rub, and serial electrocardiogram (ECG) changes. Awareness of the disease has increased due to the introduction of noninvasive diagnostic techniques such as echocardiography, CT scanning, and cardiac magnetic resonance imaging (CMRI) . The disease can be severe and even lethal, especially in immunosuppressed children. The disease causative agent can usually be identified from the pericardial fluid by culture or more sensitive tests (e.g. polymerase chain reaction - PCR or from pericardial biopsy samples).
Keywords: myocarditis; pericarditis; cardiac insufficiency